CLT in ESL and EFL Context: A Challenge to Civil Engineering Teachers in Indonesia - Endah P Haryono (Jurnal Teknik Sipil Terapan, 2019)
Characteristic and Principle of the communication approach to language learning andteaching has given appropriate and positive strategies in order to produce student’s ability incommunicative competence. One of its positive principles of this approach is students learnEnglish not in order to know the language rules but in order to use it in communication.However it can be said that this approach only gives specific advantages to ESL countries butnot for EFL context. It is because there are many EFL teachers such as English teachers inIndonesia still encounter difficulties in applying CLT in their classroom. This article givesessential solutions in order to encounter this issue towards teaching English in civil engineeringclassroom in Indonesia as EFL country. It is said that in order to accomplish the success inlanguage teaching, English teachers in civil Engineering should improve their quality incommunicative competence as well as their teaching strategy to combine and implement intocommunicative classroom approach, syllabus and material based on learner needs and interestin authentic situation.